Study on the value of Taijiquan in Healthy Chinese Vision - Zhang, Qiuyan (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: "Health is an inevitable requirement for promoting the Healthy China 2030 development and is the basic condition for economic and social development," according to the Healthy China Plan However, with the continuous improvement of people's quality of life and the continuous development of science and technology level, the reduced physical quality, aging population, disease prevention difficulties, the change of ecological environment and lifestyle have brought a series of challenges to the maintenance and promotion of health. On December 17, 2020, Taijiquan successfully applied for being a world-class intangible cultural heritage. Its unique medical value, fitness value, body defense value, cultural value and educational value have attracted the attention of the world. Therefore, the depth of mining taijiquan in the "healthy China 2030" planning outline not only to carry forward the Chinese traditional culture and improve the comprehensive quality and promote the development of Chinese social construction, is more conducive to the background of global integration for the world people to provide scientific, upward for good exercise methods, promote the harmonious development of world civilization. Methods: Literature data method, logic analysis method, expert interview method, etc. Results: Taijiquan is a skill and a culture, and the two complement each other. Behind it, it is more full of rich life science foundation, operational technical norms, social and cultural background, environmental and ecological influence and historical evolution. Under the background of the Outline of the Healthy China 2030 Plan, Taijiquan has an irreplaceable role of other sports in improving the physical quality, improving the spirit and shaping the moral character. The conclusions are drawn as follows: 1. Taijiquan for improving physical quality: 1. 1 External physical exercise. Taijiquan is obviously different from the exercise mode of a single part of the muscle groups in other sports projects. It is full of kicking, beating, throwing, taking, stabbing, cutting, cutting, splitting and blocking, which plays a very important role in promoting the muscle groups and joints of all parts of the body. In addition, taijiquan in the process of its movement and focus on the coordination between the whole body muscles and joints, each move each type requires foot bottom, waist and hip, elbow, shoulder and other parts of the coherent force, which to a large extent effective development of the human brain for the flexibility of the limbs, the human limbs balance ability and coordination ability has been significantly improved. 1.2 Formation of the inner spirit. Through experiments and investigation on some practitioners, it is found that people like Taijiquan not only because of the need for disease prevention and physical fitness, but also because of the effect of Taijiquan practice that can effectively relieve stress and negative emotions. Taijiquan technology is gentle and natural, the combination of movement and movement, stretch, rigid and softness, and beautiful movement make people integrate with nature in the process of practice, and then understand the beauty of the human mind, the beauty of life, and form a kind of upward and good mentality. 2. Taijiquan education of enhancing physical and mental literacy: the character foundation of 2. 1 "virtue". Since ancient times, the Chinese people have paid great attention to the word "virtue". Only with virtue can they be right and far away, while the country is free of virtue, and people have no virtue. Taijiquan pays great importance to etiquette, and in the process of practice, it imperceptibly shapes a spiritual quality of respecting the old and caring for the young. In addition, the practice process of Taijiquan requires meditation, that is, a state of "no". Through meditation and then introspection of the way between people, in order to cultivate the "gentleman's wind" of modern people. 2. 2 The habit of "struggle". On the one hand, Taijiquan offensive and defense technology is always inseparable from its actual needs and response situation, and it is this substantive purpose to develop justice, courage, self-defense, violence and other will qualities, so that practitioners can move forward in the face of evil and difficulties. On the other hand, the practice of Taijiquan has a certain hardship. As many folk boxers say, "boxing thousands thousand times, self-evident" and "practice in summer, practice in winter", it is through the practice of Taijiquan that practitioners are always full of the habit of "insisting on struggle" in their hearts. 2.3 A "Harmonious" attitude towards life. With the continuous development of modern science and technology, people's grab for public resources is increasingly serious, especially the law of "survival of the fittest" life is deeply rooted in the hearts of the people, which makes the tower of trust between people gradually collapse. Taijiquan, from "people-oriented" as the starting point, constructs a technical theoretical system based on "harmony", makes up for the lack of mind in the way to get along between people, society, man and nature, and plays an important role in stimulating the development of society towards civilization, freedom, equality, fairness and integrity. 3. Prevention of Taijiquan to slowing down the risk of aging society: 3.1 Scientific nature of "strong physical disease prevention". Taijiquan has an inseparable connection with traditional Chinese medicine. The earliest combination of boxing and traditional Chinese medicine should belong to the ancient medical master Hua Tuo, which clearly pointed out the effect of the boxing method to enhance the physical fitness, preventing diseases, and regulating the body and mind. Since its formation, Taijiquan has often been accompanied by the above functions, worthy of the name "medical", just as Chen Guanting's creation of Chen Taijiquan "what is the auspicious intention, prolong life is not spring". On the other hand, it is widely believed that data under modern scientific instruments thus doubt the value of Taijiquan. However, through the experimental analysis of Taijiquan by European scholars in recent years, it has fully demonstrated its unique application value. From the increasing number of European Taijiquan practitioners, we can also prove the scientific medical value of Taijiquan from the side. 3. 2 The universality of "easy to learn". On the one hand, there are many methods of Taijiquan, people can choose suitable Taijiquan according to their hobbies, such as Chen Taijiquan, Yang Taijiquan, compact and rigorous. There are also 24 simplified Taijiquan, the content is more refined and easy to learn, more convenient to spread around the world. On the other hand, it is because of the wide variety of Taijiquan and moderate intensity that the boundaries between different ages exist. For example, Taijiquan has the effect of prolonging life for the elderly, a philosophy of harmonious consciousness for young people, and a cognitive effect on the development of young people's thinking. 3.3 "radiant" nourishing. The research on the value of "radiant" of Taijiquan is still to be developed. According to the survey, it is found that the average practice is more than four times a week, and those who practice about two hours per practice are significantly different in appearance. People who often live through electronic equipment tend to have sunken eyes, yellowing faces and no spirit, while those who often participate in Taijiquan practitioners often show very energetic external characteristics such as divine eyes, ruddy complexion, and pink lips. Therefore, Taijiquan plays an obvious and important role in improving the human body's external mental temperament. 4. Taijiquan is the reflection of the excellent culture of the Chinese nation: the Chinese nation has a history of 5,000 years, and has produced rich and colorful Chinese culture, and various cultures are included among each other. Therefore, taijiquan also contains a rich Chinese culture, in its theory, easy, soldiers, medicine, the director of the family, full of the survival skills of the Chinese nation to life and natural environment, namely kick, play, fall, take, thorn, splitting, cutting and other technical action elements, is a rich true reflection of the excellent culture of the Chinese nation. Conclusion: Taijiquan plays a very important role in improving the physical quality and enhancing the physical and mental quality, which is conducive to improving the quality of the whole people while maintaining the rapid and stable development of social harmony. At the same time, in the background of the aging society, the scientific nature, simple universality and radiant nourishment of Taijiquan are of great significance to preventing and delaying the aging society. In addition, throughout the process of Taijiquan, the evaluation of Taijiquan is always useful and effective, so it can still break out strong vitality today with the rapid development of society. With the promulgation of the Outline of the Healthy China 2030 Plan, Taijiquan should show its due value for the construction of a healthy China and creating a green and healthy environment, and better meet the needs of the current people for health.